Optimizing Social Media for Hotel Marketing and Consumer Behavior Insights - Yuyun Yuniarsih; R.Ricky Agusiady (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The hospitality industry in Bandung faces intense competition, with consumer behavior increasingly shaped by social media as a source of travel information and recommendations. This study aims to analyze how hotel uses social media to strengthen marketing management and understand consumer behavior. A descriptive qualitative approach was employed, involving in-depth interviews with the hotel’s digital marketing team, questionnaires with 20 active social media users, observations of social media accounts, and analysis of promotional reports. The findings show that the hotel uses Instagram, TikTok, Facebook, and YouTube to highlight its European-style architecture, promote seasonal discounts, and collaborate with influencers, resulting in a 15% increase in bookings. Social media enables quick responses to inquiries, personalized guest communication, and insights into consumer preferences, with 70% of visitors relying on online reviews before booking and 40% attracted by photo spots. The attention, interest, search, action, share model explains how consumers engage with and share content, boosting organic promotion. This study provides practical strategies for hotels to enhance digital marketing and contributes to understanding consumer behavior in Bandung’s tourism sector, recommending further exploration of diverse platforms and larger samples.